Antibacterial activity of salicylanilide 4-(trifluoromethyl)-benzoates - Krátký, Martin; Vinšová, Jarmila; Novotná, Eva; Mandíková, Jana; Trejtnar, František; Stolaková, Jiřina (Molecules (Basel, Switzerland), 2013)
The development of novel antimicrobial agents represents a timely research topic. Eighteen salicylanilide 4-(trifluoromethyl)benzoates were evaluated against Mycobacterium tuberculosis, M. avium and M. kansasii, eight bacterial strains including methicillin-resistant Staphylococcus aureus (MRSA) and for the inhibition of mycobacterial isocitrate lyase. Some compounds were further screened against drug-resistant M. tuberculosis and for their cytotoxicity. Minimum inhibitory concentrations (MICs) for all mycobacterial strains were within 0.5-32 μmol/L, with 4-chloro-2-[4-(trifluoromethyl)phenylcarbamoyl]phenyl 4-(trifluoromethyl)benzoate superiority. Gram-positive bacteria including MRSA were inhibited with MICs ³ 0.49 μmol/L, while Gram-negative ones were much less susceptible. Salicylanilide 4-(trifluoromethyl)benzoates showed significant antibacterial properties, for many strains being comparable to standard drugs (isoniazid, benzylpenicillin) with no cross-resistance. All esters showed mild inhibition of mycobacterial isocitrate lyase and four compounds were comparable to 3-nitropropionic acid without a direct correlation between in vitro MICs and enzyme inhibition.
Keywords: Mycobacterium tuberculosis; mikrobiální testy citlivosti; Propionates; Mycobacterium kansasii; Anti-Bacterial Agents; Mycobacterium avium; methicilin rezistentní Staphylococcus aureus; salicylanilidy; isocitrátlyasa; Nitro Compounds; Microbial Sensitivity Tests; benzoáty; Benzoates; dusíkaté sloučeniny; antibakteriální látky; propionáty; Isocitrate Lyase; Salicylanilides; Methicillin-Resistant Staphylococcus aureus